DEVELOPING GUIDEBOOK OF WRITING INSTRUCTIONAL TEXTS BY USING DRAWING CARDS FOR FOURTH GRADE STUDENTS (Universitas Negeri Semarang, 2017)
The objectives of this study were to develop a guidebook of writing instructional texts by using drawing cards, describe media and materials experts' judgements against the guidebook prototype, and describe the effectiveness of the guidebook in limited tryout to the students of IV-A class, State Elementary School (SDN) Tambakaji 05, Semarang City. This study employed research and development (RD) design with seven steps. The data were collected through need questionnaires and validation sheet questionnaires. Further, the results of this study were: (1) there were found three needs of teachers and students, namely, (a) The appearance of the guidebook with the criteria of rectangular shape, small size or A5, between 20-40 pages of book thickness, white-colored paper, having pictures and illustrations, colored drawings and illustrations, and full color book covers, (b) match with basic competencies and instructional themes; (c) standardized language use and various sentences; (d) chronological material presentation in presenting learning objectives, materials, interesting book design, exercises, and the balance amount of evaluation exercises with the materials; (2) there found very valid category in experts' judgement steps, namely 93.05%; (3) the same category was also found in the limited tryout to the students of IV-A class, SDN Tambakaji 05, Semarang City whose average was 85.41. From these findings, it can be concluded that the guidebook of writing instructional texts by using drawing cards is feasible and effective to use in learning process and can improve the fourth grade students' learning achievement.